2019
DOI: 10.36348/sjpm.2019.v04i10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity among Type 2 Diabetic Patients Attending Diabetes Clinics in Sokoto Northwestern Nigeria

Abstract: Diabetes, is a metabolic disease, and is one of the most common endocrine disorders affecting almost 6% of the world's population. This study intends to determine the prevalence of obesity and risk factors among type 2 diabetic patients, with the aimed of providing some possible measures to the finding in order to improve the level of health care rendered to the patients. This was a hospital-based retrospective study carried out at metabolic clinic of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…A statistically significant association was found between age group of the patient and body mass index. This was in agreement with finding by Kasimu et al [2] in North-West Nigeria.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…A statistically significant association was found between age group of the patient and body mass index. This was in agreement with finding by Kasimu et al [2] in North-West Nigeria.…”
Section: Discussionsupporting
confidence: 94%
“…A significant association was found between the sex of the patient and their body mass index. This was supported by other researchers [2,12,13,16]. The married constituted more than three quarter of the study participants and this agrees with Murad et al [20] A significant association was found between marital status and BMI in this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations